2010
DOI: 10.1093/cercor/bhq145
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Responses for the Expectation of Juice and Money Rewards in Human Ventromedial Prefrontal Cortex

Abstract: Although much is known about the neural substrates of reward, the question of whether expectation of different types of reinforcers engage distinct or overlapping brain circuitry has not been addressed definitively. In the present study, human subjects, while being scanned with functional magnetic resonance imaging, performed a simple reward-based action selection task to obtain different magnitudes of either monetary outcomes (winning or losing money) or juice outcomes (pleasant apple juice or an unpleasant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
118
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 46 publications
16
118
2
1
Order By: Relevance
“…Consistent with the strong consensus in the adult literature (8), we observed activation of MPFC and DLPFC and adjacent cortical regions during EV computations. Our observation of decreased activation in insula in response to increasing EV is also supported by existing findings (23,26). However, we observed robust developmental differences in the VS, such that adolescents exhibited significantly greater activation than adults (who showed virtually no activation in this region), suggesting that maturational changes in neural representation of valuation during adolescence are most robust in the VS.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the strong consensus in the adult literature (8), we observed activation of MPFC and DLPFC and adjacent cortical regions during EV computations. Our observation of decreased activation in insula in response to increasing EV is also supported by existing findings (23,26). However, we observed robust developmental differences in the VS, such that adolescents exhibited significantly greater activation than adults (who showed virtually no activation in this region), suggesting that maturational changes in neural representation of valuation during adolescence are most robust in the VS.…”
Section: Discussionsupporting
confidence: 90%
“…In previous work, increased neural connectivity between insula and MPFC during the processing of self-relevant information has been shown, (Schmitz and Johnson, 2006), which may represent the pathway by which self-schemabased core value information is integrated into evaluative representations in the insula. However, up to now, brain imaging studies have not been able to reveal how the insula represents emotional and value-related information, as insula activation does not show linear increases or hemispheric asymmetries according to stimulus valence (Lamm and Singer, 2010, but see Kim et al, 2011). It was recently suggested that different neuronal ensembles lying in close proximity in the insula may code for negative and positive affect, and that standard coarse-grained fMRI analysis techniques may therefore not be able to separate the information (Lamm and Singer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These computations involve regions such as the orbitofrontal cortex (OFC)/ventromedial prefrontal cortex (VMPFC), the ventral striatum and the insula, a network activated by many different types of rewarding stimuli such as food, juice, money or attractiveness (Knutson et al, 2003;Kawabata and Zeki, 2004;O'Doherty, 2004;Kim et al, 2011). When comparing the effects of different rewarding stimuli in the same subjects, overlapping activations were observed in VMPFC and insula, suggesting that these regions represent the common currency for different types of rewarding stimuli (Kim et al, 2011). The activation of value-related regions reflects individual preferences and, therefore, choices, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Following the utility concept put forward by utilitarian philosophers and used by economists, it has been suggested that the brain performs decisions between such dissimilar options by assigning a value to each of them, which is mapped on a common scale of desirability regardless of the specific type of option (Montague and Berns, 2002;Fehr and Rangel, 2011;Levy and Glimcher, 2012). In line with the hypothesis of a common scale of subjective value, human functional magnetic resonance imaging (fMRI) studies have observed an overlap of value-related signals in the medial prefrontal cortex (mPFC) for different types of reward, such as consumer goods, monetary rewards, and also social rewards (Chib et al, 2009;FitzGerald et al, 2009;Lebreton et al, 2009;Smith et al, 2010;Kim et al, 2011;Levy and Glimcher, 2011;Lin et al, 2012). Further, it has been demonstrated that value signals for money and food options do not only spatially overlap, but that equally preferred money and food options elicit comparable BOLD responses in the mPFC both univariately (Levy and Glimcher, 2011) and multivariately (McNamee et al, 2013).…”
Section: Introductionmentioning
confidence: 92%